2018
DOI: 10.4103/bc.bc_7_18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischemic preconditioning on mitochondrial and metabolic neruoprotection: 5' adenosine monophosphate-activated protein kinase and sirtuins

Abstract: Stroke and cardiac arrest result in cerebral ischemia, a highly prevalent medical issue around the world, which is characterized by a reduction or loss of blood flow to the brain. The loss of adequate nutrient supply in the brain during ischemia results in neuronal cell death contributing to cognitive and motor deficits that are usually permanent. Current effective therapies for cerebral ischemia are only applicable after the fact. Thus, the development of preventative therapies of ischemia is imperative. A fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Furthermore, IPC treatment also remarkably improves the metabolic disturbances in the TCA cycle during ischemia. IPC has also demonstrated neuroprotective activity through the activation of Nrf2 both in vivo and in vitro, which is a transcription factor that helps to maintain mitochondrial coupling and antioxidant protein expression [ 75 ]. This described evidence highlights the capability of IPC in improving mitochondrial efficiency and regulating the reprogramming processes related to mitochondrial function and cellular metabolism.…”
Section: Metabolic Reprogramming In Ischemic Stroke Treatment By Ischemic Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IPC treatment also remarkably improves the metabolic disturbances in the TCA cycle during ischemia. IPC has also demonstrated neuroprotective activity through the activation of Nrf2 both in vivo and in vitro, which is a transcription factor that helps to maintain mitochondrial coupling and antioxidant protein expression [ 75 ]. This described evidence highlights the capability of IPC in improving mitochondrial efficiency and regulating the reprogramming processes related to mitochondrial function and cellular metabolism.…”
Section: Metabolic Reprogramming In Ischemic Stroke Treatment By Ischemic Preconditioningmentioning
confidence: 99%
“…PPFKFB3 controls glycolytic flux by synthesizing fructose-2,6-bisphosphate (F2,6BP), a potent allosteric activator of phosphofructokinase 1 (PFK-1), which is a master regulator of glycolysis [ 18 ]. Furthermore, the level of glycolytic products of lactate in CSF was found to be decreased following IPC [ 75 ]. Altogether, these results imply that subduing postischemic hyperglycolysis and the regulation of brain glucose metabolism play important roles in the neuroprotective aspect of IPC.…”
Section: Metabolic Reprogramming In Ischemic Stroke Treatment By Ischemic Preconditioningmentioning
confidence: 99%
“…However, nitrous oxide preconditioning had little or no neuroprotective effect in focal or global ischemia models, it may even repress the neuroprotective effects when used in conjugation with other inhalational anesthetics (73). Jackson et al (88) preconditioned rats with daily metformin treatments for 2 weeks before transient forebrain global ischemia. They found that metformin preconditioning increased mitochondrial biogenesis and reduced apoptotic cell death (88).…”
Section: Chemical/pharmacological Preconditioningmentioning
confidence: 99%
“…Jackson et al (88) preconditioned rats with daily metformin treatments for 2 weeks before transient forebrain global ischemia. They found that metformin preconditioning increased mitochondrial biogenesis and reduced apoptotic cell death (88). Research showed that dexmedetomidine preconditioning could protect against global cerebral ischemic injury following cardiac arrest and was associated with increased HIF-1α and VEGF expression (89).…”
Section: Chemical/pharmacological Preconditioningmentioning
confidence: 99%
“…The underlying mechanisms have not been fully deciphered yet. The process by which this tolerance develops is highly complex, involving a profusion of signaling pathways and their mediators [for example, the Janus-activated kinase (JAK) and PKC], as well as gene expression, together responsible for sensing, transducing, modulating, and effecting preconditioned resistence; these include adenosine, excitatory and inhibitory amino acids (for example, glutamate and γ-amino-butyric acid), reactive oxygen species (for example, O 2 , H 2 O 2 , and OH), transcription factors (for example, NF-kappaB and HIF-1), membrane channels (for example, calcium ions and ATP-sensitive K + channels), heat shock proteins (for example, Hsp-70 and Hsp-27), cytokines (for example, IL-6, IL-1βand TNF-α), and mitochondrial biogenesis (Hagberg et al, 2004;Lu et al, 2005;Long et al, 2006;Marini et al, 2007;Dornbos and Ding, 2012;Thompson et al, 2012;Cai et al, 2014;Chen et al, 2016;Mukandala et al, 2016;Basheer et al, 2018;Jackson et al, 2018). In general, the neuroprotective effect of HPC/IPC appears to depend on both the downregulation of detrimental cellular mediators and biomolecules, and the upregulation of their beneficial counterparts (Lu et al, 2005).…”
Section: Hypoxic/ischemic Preconditioning (Hpc/ipc) and Endogenous Nementioning
confidence: 99%